PROPERTY-SYNDICATION INVESTMENT V PROPERTY SCAM: WHO DECIDES? A CRITICAL EXAMINATION OF THE REGULATION OF PUBLIC-PROPERTY SYNDICATION SCHEMES IN SOUTH AFRICA - Tanya Woker (Obiter, 2021)
Building an investment portfolio is an important part of saving for retirement. This not only benefits the individual concerned but it also has benefits for the economy as a whole. Investment in property is regarded as an essential element of an investment portfolio and many investors have over the years invested in public-property syndications. Unfortunately such investments have proved to be very risky and there have been some spectacular failures with severe consequences especially for elderly, vulnerable consumers. There is a need to ensure that all investment opportunities are properly regulated and different aspects of property syndications are regulated by different regulators including the Reserve Bank, the Department of Trade and Industry, the newly established Consumer Commission and the Financial Services Board. There seems to be some confusion amongst regulators over which entity is ultimately responsible for ensuring that such investments are sound and reliable and that consumers can have faith that they are not investing in a scam. The fact that no one regulator is responsible for overseeing the full picture is problematic because it enables the unscrupulous to slip under the radar and avoid detection. This paper seeks to consider the question of which regulator is or should be responsible for regulating public-property syndications and to make some suggestions for reform going forward.